A DIGITAL TECHNIQUE FOR CONVERTING PARTIAL DENTURES INTO IMMEDIATE FULL DENTURES - Ana Petre; Andreea Baluta; Ioana Becheru; Sorina Stroe; Ruxandra Sfeatcu; Stefan Milicescu (Romanian Journal of Oral Rehabilitation)
The increasingly complete integration of digital techniques into the routine of dental clinics allows doctors to carry out classic treatments in a much simpler, more efficient and comfortable way for patients. The clinical situations that involve the transformation of removable partial dentures into complete dentures, require an immediate resolution for the aesthetic dysfunction determined by the extraction of the remaining teeth. It is unacceptable to leave the patients with aesthetic dysfunction, even for short periods of time. This article proposes a digital technique which transforms acrylic partial dentures into complete dentures before dental extractions, so that the patient leaves the dental office on the day of the extractions with a prosthetic denture. This procedure eliminates several mandatory steps in the protocol of making acrylic complete dentures and, in addition, we eliminate the risk of accidental extractions during conventional impression. Providing immediate digital prostheses to patients is a modern and viable trend.